(untitled) (Research, Society and Development, 2021)
In Indonesia, development of application of good faith principle in legal agreement focuses on the application of Civil Code (KUHPerdata) where scope is still placed on the implementation of agreement. It is as if Civil Code has not recognized the existence of good faith principle at pre-contract stage. In comparison, according to modern agreement theory that parties who suffer losses in pre-agreement/contract stage or at negotiation stage, their rights also deserve to be protected. Thus, pre-agreement/contract promises will have legal implications for those who violate them. This will be seen in countries that have common law and civil law systems. An important issue in this case relates to the principle of good faith at the pre-contract stage which creates a gap with the provisions in the legislation. To analyze these problems, legal research was conducted with the black-letter law paradigm. Technique of collecting legal materials in this research used library research. Legal materials are analyzed deductively and utilize the method of interpretation (hermeneutics). Results showed that the application of the principle of good faith at the pre-contract stage in Common Law and Civil Law countries had differences. In the Civil Law system, good faith is highly emphasized in the stage of contractual negotiation. Whereas in the Common Law system, it prioritizes efforts to restore rights of aggrieved party in pre-contract stage. Parties who do not have good faith at the pre-contract stage have legal consequences for cancellation of the agreement.